Corroding Armed Conflicts through Peacebuilding Initiatives in Northeast Nigeria - Emmanuel, Joseph (Darul Yasin Al Sys, 2025)
The Northeast region of Nigeria has faced protracted armed conflict driven by the Boko Haram insurgency, its offshoots such as the Islamic State West Africa Province (ISWAP), and other forms of violence including banditry and communal clashes. These conflicts have precipitated widespread humanitarian crises, mass displacement, and profound socio-economic instability. In response, diverse peacebuilding initiatives have been deployed to weaken insurgent influence and restore regional stability. This article examines a range of peacebuilding efforts, encompassing government-led interventions, civil society and NGO programs, religious and community-based strategies, and international support mechanisms. Key approaches include grassroots dialogue, disarmament and demobilization programs, the rehabilitation of former insurgents, and youth empowerment schemes aimed at fostering community resilience. While notable progress has been achieved, peacebuilding in the region continues to face significant challenges such as persistent insecurity, intercommunal distrust, institutional fragility, and entrenched cultural barriers. The study emphasizes the need for a more inclusive, sustainable peacebuilding framework that integrates women and youth in peace processes and leverages indigenous conflict resolution practices. Recommendations include strengthening local peace infrastructures, improving monitoring and evaluation systems, enhancing inter-stakeholder collaboration, and investing in education and socio-economic development to sustain peace efforts. A comprehensive, well-resourced, and participatory strategy remains vital to disrupting cycles of violence and promoting long-term peace and social cohesion in Northeast Nigeria.